ASSESSMENT OF NON-FORMAL AND INFORMAL LEARNING OUTCOMES AT THE UNIVERSITY: POLITICAL AND THEORETICAL PERSPECTIVE - Burkšaitienė, Nijolė (Acta Paedagogica Vilnensia, 2009)
The present study analyses the problem of assessment of non-formal and informal learning at universities from the perspective of general systems theory. It aims at analysing assumptions for the assessment and recognition of non-formal and informal learning created in the EU and national documents on education policy and identifies peculiarities of assessment of such learning at universities.Drawing together the evidence gleaned from the EU and national documents on education policy, from the available research data and from the comparative analysis of assessment of formal, non-formal and informal learning outcomes at universities it has been established that:1. Assessment of non-formal and informal learning at the university is an integral part of a wider system comprising three subsystems: teaching-learning-assessment. As a subsystem it influences the system itself and has an impact on the non-academic system of learning-teaching-assessment existing outside the university.2. Assumptions for the creation and implementation of assessment and recognition systems have been created on the European and national level. In Lithuania universities are preparing to start assessing and recognising outcomes of non-formal and informal learning.3. The principle goal of assessing non-formal and informal learning at the university is to establish if the learning that occurred in different learning environments is equal to that occurring at the university.Portfolio method has been acknowledged as the most effective method used at the university for the purpose defined above. The choice of supplementary methods of assessment depends on the specificity of the course, a course program or a module.Finally, assessment of non-formal and informal learning at the university should be carried out by a panel of assessors comprising university teachers and experts form the world of work. This yields some advantages: a candidate’s capacity to use his knowledge in practice is assessed objectivity of assessment is ensured, the link between academic and the real world of work is established.
Keywords: non-formal learning; informal learning; assessment; political perspective